Gaining of competitive advantage of Malaysian telecommunication products: measure of competitiveness - Haque, A. K. M. Ahasanul; Sultana, Seyama; Kedah, Zulkarnain; Yasmin, Farzana; Momen, Abdul (World Business Institute, 2014)
This study tries to examine the export competitiveness of selected telecommunication products by using indicators like Revealed Comparative Advantage (RCA) and Constant Market Share (CMS) analysis and Shift-share method and these are used for identifying potential export markets. The selected four categories of telecommunication products are taken into account on the basis of three digit level Standard International Trade Classification (SITC) for the period between 2000 and 2011.The RCA calculation clearly indicates an increasing strength of comparative advantage of Malaysia, except for the products (SITC- 763) and (SITC- 764). This is mainly due to the negligible import for these products. The CMS results suggest that export gains of Malaysia for telecommunication products are largely attributed to the size of the market and also to its competitiveness effects. The CMS analysis also depicts that the competitiveness effect of telecommunication products are subsequently improved in general during the period III and I (2008-11and 2000- 03) as compared to those of the period I and II (2000-03 and 2004-07) and period II and III (2004-07 and 2008-11). The shift- share indicates that the USA, UK, Netherlands, Switzerlands, Japan and Germany are biggest importing countries of Malaysian telecommunication products although major challenges are the asian countries here.